AUDIENCE SEGMENTATION BASED ON FASHION INDUSTRY MARKETING STRATEGIES (Marketing Journal, 2025)
The article examines theoretical approaches to audience segmentation within marketing strategies in the fashion industry. The structure of the STP model is applied to explain the logical relationship between segmentation, targeting, and positioning stages. Demographic, psychographic, and technological segmentation criteria are identified under conditions of digital transformation. The effectiveness of strategies is supported through theoretical constructs and recent empirical sources. The need for segment -specific solutions is emphasized. Conclusions and recommendations are aligned with contemporary marketing frameworks.
Keywords: marketing strategy; segmentation; STP model; fashion industry; targeting; positioning; digital marketing. 629